2017
DOI: 10.1016/j.jmatprotec.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of pulsed laser and pulsed TIG welding of Ti-5Al-2.5Sn titanium alloy sheet

Abstract: Pulsed Nd:YAG laser beam welding (P-LBW) and pulsed tungsten inert gas (P-TIG) welding were used to prepare full penetration bead-on-plate weldments of 1.6 mm thick Ti-5Al-2.5Sn alpha titanium alloy sheet. The influence of welding phenomenon on the microstructure, micro-hardness, tensile properties, surface and sub-surface residual stress distribution and deformation and distortion of both the weldments were studied. Higher cooling rate in P-LBW resulted in complete ␣' martensitic transformation in fusion zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 47 publications
1
39
0
3
Order By: Relevance
“…To protect the molten titanium pool from oxidation, the flow of argon with a flow rate in the range 10 to12 L/min was maintained during and after the welding operation. The details of residual stress measurement procedure and microscopy are given in detail in the author's previous work 15 .…”
Section: Methodsmentioning
confidence: 99%
“…To protect the molten titanium pool from oxidation, the flow of argon with a flow rate in the range 10 to12 L/min was maintained during and after the welding operation. The details of residual stress measurement procedure and microscopy are given in detail in the author's previous work 15 .…”
Section: Methodsmentioning
confidence: 99%
“…This can be explained in terms of the presence of α and β phases in both the L-HAZ and BM. Indeed, due to a small testing zone (about 5 µm) and coarser α and β sizes, depending on whether the measurement location was on α or β phase, a different chemical composition was measured as these alloying elements have different affinities for α and β phases [33]. …”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…The research on the joining of TC4 alloy has been well reported, such as tungsten inert-gas welding (TIG) [4][5][6], metal inert-gas welding (MIG) [7], electron beam welding [8][9][10][11], laser beam welding [12][13][14], and laser-MIG hybrid (LAMIG) welding [15,16]. Among these welding techniques, LAMIG welding is suitable for the joining of TC4 alloy.…”
Section: Introductionmentioning
confidence: 99%